The Relation between Protein Malnutrition, Ethanol Consumption and Chromosomal Damage Induced by Cyclophosphamide in Bone Marrow Cells of Mice - Terreros, M. C. (1995)
The effect of protein malnutrition and alcohol consumption on the yield of chromosomal damage induced by cycloPhosphamide (CP) was studied. Chromosomal damage induced in bone marrow cells of BALB/c mice was established by scoring the frequency of dicentric chromosomes in C-banded slides. Results obtained showed that CP induced a significant increase of chromosomal damage in comparison with untreated mice. In addition, the yield of dicentric chromosomes was higher in mice fed with the hypoproteic diet. The animals which received ethanol in drinking water before treatment with CP exhibited the highest frequency of dicentric chromosomes, with no relation with the diet. Statistical analysis of these results showed the additive effect of diet and CP and are explained taking into account the metabolic pathways of CP as well as the decrease of enzymatic levels and the physiological condition in under-nourished mice.